Antimicrobial activity and bioautographic study of antistaphylococcal components from Caesalpinia pyramidalis Tull. - Antonio Marcos Saraiva; Cristiane Lopes Saraiva; Admário Marques Gonçalves; Rogério Ribeiro Soares; Fabrício de Oliveira Mendes; Risonildo Pereira Cordeiro; Haroudo Satiro Xavier; Maria Nelly Caetano Pisciottano (Universidade de São Paulo, 2012)
The antimicrobial activity of dry methanol and ethyl acetate extracts for the leaves, bark of the stem, peel of the root, flower, fruit and seed of Caesalpinia pyramidalis Tull. (catingueira) was performed against seventeen isolates of Staphylococcus aureus MRSA multiresistant strains, which included two isolates of S. aureus MSSA and two ATCC strains. The antimicrobial activity was tested by the agar diffusion method and the Minimum Inhibitory Concentration (MIC) was determined. The dry methanol extract of the root showed good antimicrobial activity with a MIC of less than 0.5 mg.mL-1. The dry ethyl acetate extracts exhibited lower antimicrobial activity, which might be explained by solubility problems and less diffusion in the agar medium. Results of the bioautographies also confirmed inhibition halos corresponding to the active substances present in the leaves, as well as in the flower of C. pyramidalis. The phytochemical study of the leaves, bark of the stem, peel of the root, flower and fruit of extracts from C. pyramidalis confirmed the presence of a number of known antimicrobial agents including ursolic acid, quercetin, catechin, ellagic acid, sitosterol, flavonoids, proanthocyanidins and gallic acid. A determinação da atividade antimicrobiana dos extratos metanólicos e em acetato de etila da folha, casca do caule, casca da raiz, flor, fruto e semente de Caesalpinia pyramidalis Tull. foi realizada frente a dezessete isolados de Staphylococcus aureus MRSA multirresistentes, dois isolados de S. aureus MSSA e duas cepas padrão, pelas técnicas de poço/difusão em ágar e determinação das CMI pelo método de diluição em agar/multiinoculador de Stears. O extrato metanólico de casca da raiz indicou uma boa atividade, com CMI inferior a 0.5 mg.mL-1. Os extratos secos por extração em acetato de etila apresentaram menor atividade que se poderia explicar por problemas de solubilidade e menor difusão no meio de cultura em ágar. Resultados das bioautografias confirmaram zonas de inibição correspondente às substâncias ativas presente na folha, como também na flor da C. pyramidalis. No estudo fitoquímico das folhas, casca da caule, casca da raiz, flor e fruto dos extratos de C. pyramidalis evidenciou-se a presença de vários constituintes com reconhecida atividade antimicrobiana, entre estes o ácido ursólico, quercetina, catequina, ácido elágico, sitosterol, flavonóides, proantocianidinas e ácido gálico. Entre todos os metabólitos citados, somente o ultimo não observamos, por CCD, na casca da raiz de C. pyramidalis.